The Juridical Review of Fluctuations Land Lease Prices of The Pendem System In Kesilir Village Banyuwangi - Veny Widayanti; Mahbub Ainur Rofiq; Lempang Hasibuan (Program Studi Hukum Keluarga Islam, 2022)
The pendem system is a land lease with a period of more than two consecutive years with depreciation payments, in the first year the rental price is normal, then for the next year, there is a depreciation of rental costs. Payment of rental fees can be made at the beginning, in the middle, or at the end of the rental period according to the agreement of the parties. however, there is an additional rental fee in the payment in the middle or at the end of the rental period which was not stated at the beginning of the agreement. The purpose of this study is to find out the legal validity of land leases with a pendem system based on Islamic law and the Indonesian Civil Code. This research is field research with a sociological juridical approach. The primary data were obtained from interviews with the parties, while the secondary data was obtained from books and journals that discussed land renting. The results of this study indicate that the terms of ijarah related to the clarity of the rental fee have not been fulfilled, because there are additional costs for payments in the middle or at the end of the lease period that were not stated at the beginning of the agreement. The addition contains an element of usury nasi'ah, which is an addition that is mentioned in the agreement for the exchange of goods in exchange for the delay in payment. The existence of these additional fees makes the transaction law invalid.Sistem pendem adalah sewa tanah dengan jangka waktu lebih dari dua tahun berturut-turut dengan pembayaran penyusutan, pada tahun pertama harga sewa normal, kemudian untuk tahun berikutnya terjadi penyusutan biaya sewa. Pembayaran biaya sewa dapat dilakukan di awal, di tengah, atau di akhir masa sewa sesuai kesepakatan para pihak. namun terdapat tambahan biaya sewa dalam pembayaran di tengah atau di akhir masa sewa yang tidak disebutkan di awal perjanjian. Tujuan dari penelitian ini adalah untuk mengetahui keabsahan hukum sewa tanah dengan sistem pendem berdasarkan hukum Islam dan Kitab Undang-Undang Hukum Perdata Indonesia. Penelitian ini merupakan penelitian lapangan dengan pendekatan yuridis sosiologis. Data primer diperoleh dari hasil wawancara dengan para pihak, sedangkan data sekunder diperoleh dari buku dan jurnal yang membahas tentang persewaan tanah. Hasil penelitian ini menunjukkan bahwa syarat ijarah terkait kejelasan biaya sewa belum terpenuhi, karena terdapat biaya tambahan untuk pembayaran di tengah atau di akhir masa sewa yang tidak disebutkan di awal masa sewa. persetujuan. Tambahan itu mengandung unsur riba nasi'ah, yaitu tambahan yang disebutkan dalam perjanjian penukaran barang dengan imbalan keterlambatan pembayaran. Adanya biaya tambahan tersebut membuat hukum transaksi menjadi tidak sah.